Operations Engineering for Food Warehousing Improvement: A Case Study From the Navy - Frias, Armindo; Delaunay, Rodrigo; B. Água, Pedro (International Journal of Industrial Engineering and Management, 2021)
Global competition and public awareness drive organizations to improve their management processes, including those related to logistics and warehousing. With the aim of improving the efficiency and safety of the food warehousing processes, an analysis of the warehouse layouts and storage areas layouts was carried out. Through the reorganization of the space and the review of storage policy, a practical proposal was made. To obtain more efficiency, an improved equation for the calculation of the distances travelled within the warehouse was defined. The implementation of the proposed improvements provides efficiency to warehousing, taking the Navy food central warehouse as a real case study. Article history: Received (March 16, 2021); Revised (July 14, 2021); Accepted (July 17, 2021); Published online (September 10, 2021)